PEDOGENESIS FACTORS. EVOLUTION OF SCIENTIFIC THOUGHT - ZLOBENKO, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The pedogenic factors are considered in context of research of V.V. Dokuchaev and soil scientists of latter generations.